Learning hand in hand: Engaging in research–practice partnerships to advance developmental science. Issue 172 (13th September 2020) - Mulvey, Kelly Lynn; McGuire, Luke; Hoffman, Adam J.; Hartstone‐Rose, Adam; Winterbottom, Mark; Balkwill, Frances; Fields, Grace E.; Burns, Karen; Drews, Marc; Chatton, Melissa; Eaves, Natalie; Law, Fidelia; et al.
Abstract: Developmental science research often involves research questions developed by academic teams, which are tested within community or educational settings. In this piece, we outline the importance of research–practice partnerships, which involve both research and practice‐based partners collaborating at each stage of the research process. We articulate challenges and benefits of these partnerships for developmental science research, identify relevant research frameworks that may inform these partnerships, and provide an example of an ongoing research–practice partnership.